Integrating BIM-Based LCA and Building Sustainability Assessment - Carvalho, José Pedro Almeida (2020)
With the increasing concerns about building environmental impacts, building information modelling (BIM) has been used to perform different kinds of sustainability analysis. Among the most popular are the life cycle assessment (LCA) and building sustainability assessment (BSA). However, the integration of BIM-based LCA in BSA methods has not been adequately explored yet. This study addresses the relation between LCA and BSA within the BIM context for the Portuguese context. By performing an LCA for a Portuguese case study, a set of sustainability criteria from SBTool were simultaneous assessed during the process. The possibility of integrating BIM-based LCA into BSA methods can include more life cycle stages in the sustainability assessment and allow for normalising and producing more comparable results. BIM automates and connects different stages of the design process and provides information for multi-disciplinary data storage. However, there are still some constraints, such as different BSA/LCA databases and the necessity to manually introduce the embodied life cycle impacts of building materials. The scope of the BSA analysis can be expanded by integrating a complete LCA and be fostered by the support of BIM, effectively improving building sustainability according to local standards.